Exploring the past of Mavrovouni forest in the Pindus Mountain range (Greece) using tree rings of Bosnian pines - Anastasia Christopoulou; Nikolaos M. Fyllas; Barbara Gmińska-Nowak; Yasemin Özarslan; Margarita Arianoutsou; Robert Brandes; Tomasz Ważny (Trees, 2022)
Key message Long Bosnian pine chronologies from different mountains are shaped by different climatic parameters and can help identify past drought events and reconstruct landscape histories. Abstract We developed a 735-year-long Pinus heldreichii chronology from the southern distribution limit of the species, expanding the available database of long Bosnian pine chronologies. Tree-ring growth was mainly positively correlated with growing degree days (GDD: r 1950–2018 = 0.476) while higher temperatures during both winter and growing season also enhanced growth ( T WT : r 1950–2018 = 0.361 and T GS : 0.289, respectively). Annual precipitation, during both calendar and water years, had a negative but weaker impact on annual tree growth. The newly developed chronology correlates well with chronologies developed from the neighboring mountains. The years with ring width index (RWI) lower than the average were found to correspond to cool years with dry summers. Still, the newly developed chronology was able to capture severe drought events, such as those in 1660, 1687, and 1725. Several old living trees had internal scars presumably caused by fires. Therefore, old mature trees could be used for fire history reconstruction in addition to climate reconstruction. Although the presence of lightning scars indicates an important natural agent of fire ignition, human activities associated with animal grazing could also be an underlying reason for fires in the region.